Formal Total Synthesis of (–)-5,6-Dihydrocineromycine B - Reddy, G. Venkateswar; Kumar, R. Sateesh Chandra; Siva, B.; Babu, K. Suresh; Rao, J. Madhusudana (Synlett, 2012)
An efficient and highly convergent formal total synthesis of the 14-membered macrolide (–)-5,6-dihydrocineromycine B is achieved. Key reaction sequences include a Sharpless asymmetric epoxidation followed by esterification for the formation of a fully functionalized acyclic precursor, Corey–Bakshi–Shibata reduction, and ring-closing metathesis, respectively.
Keywords: antibiotic macrolide; (–)-5,6-dihydrocineromycine B; Sharpless asymmetric epoxidation; CBS reduction; ring-closing metathesis